2021
DOI: 10.3892/etm.2021.10782
|View full text |Cite
|
Sign up to set email alerts
|

Value of GastroPanel in the diagnosis of atrophic gastritis

Abstract: Analysis of serum biomarkers for the assessment of atrophic gastritis (AG), considered as precursor of the intestinal type of gastric cancer, is of growing interest. The combination of pepsinogen (PG), gastrin-17 (G17) and anti- Helicobacter pylori ( H. pylori ) antibody serological assays (panel test) is a non-invasive tool for the diagnosis of atrophic gastritis. However, the diagnostic reliability of this test remains uncertain. The aim of our study was to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…In some previous studies, based on Biohit's claims, the GastroPanel kit has been proposed as a non-invasive method for diagnosing gastric atrophy, as well as various degrees of atrophy. 10,[14][15][16] Nevertheless, there is some controversy about this issue, 17 and the results of the present study did not confirm this assumption.…”
Section: Discussioncontrasting
confidence: 85%
“…In some previous studies, based on Biohit's claims, the GastroPanel kit has been proposed as a non-invasive method for diagnosing gastric atrophy, as well as various degrees of atrophy. 10,[14][15][16] Nevertheless, there is some controversy about this issue, 17 and the results of the present study did not confirm this assumption.…”
Section: Discussioncontrasting
confidence: 85%
“…The GastroPanel test is widely used for risk stratification 18 ; nonetheless, there are concerns regarding I/II ratios. Recent studies reported that I/II ratios did not correlate with the severity or location of atrophy when using the GastroPanel test 19,20 . Another study concluded that the GastroPanel test is insufficient for cancer screening because only 32.4% of gastric cancer patients showed low I/II ratios of <3 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that I/II ratios did not correlate with the severity or location of atrophy when using the GastroPanel test. 19,20 Another study concluded that the GastroPanel test is insufficient for cancer screening because only 32.4% of gastric cancer patients showed low I/II ratios of <3. 21 In our study, low I/II ratios and high G-17 levels correlated well with atrophy and IM scores according to the Kyoto classification.…”
Section: Discussionmentioning
confidence: 99%
“…New evidence has been published for the diagnostic performance indices of GP for both AG and HP infection. [29][30][31][32]…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…To our knowledge, there are no meta-analyses on diagnostic accuracy of GP for HP infection. New evidence has been published for the diagnostic performance indices of GP for both AG and HP infection 29–32…”
Section: Introductionmentioning
confidence: 99%